Strong Convergence Theorems for Equilibrium Problems and k-Strict Pseudocontractions in Hilbert Spaces - Dao-Jun Wen (Abstract and Applied Analysis)
We introduce a new iterative scheme for finding a common element of the set of solutions of an equilibrium problem and the set of common fixed point of a finite family of k-strictly pseudo-contractive nonself-mappings. Strong convergence theorems are established in a real Hilbert space under some suitable conditions. Our theorems presented in this paper improve and extend the corresponding results announced by many others.